THE ROLE OF ARTIFICIAL INTELLIGENCE IN THE ENGLISH LANGUAGE TEACHING PROCESS - Shokhista Khidiraliyeva, (TADQIQOTLAR, 2026)
Annotation:  The  paper  gives  information  about  the  growing  influence  of Artificial Intelligence (AI)  in the field of the English language teaching process and  analyzes the pedagogical role of AI in improving instructional effectiveness through individualized  learning,  language  skill  enhancement,  automated  assessment,  and professional support for teachers.